The Effect of Operating Room Tour Video on Pre-Anesthetic Anxiety in Sectio Caesarea Patients - Intania Muthmainnah Sastiyana; Roro Lintang Suryani; Murniati (Global Indonesia Health Care (GOICARE), 2024)
Background: Preoperative anxiety in patients undergoing cesarean sections (CS) can significantly impact both psychological well-being and physiological responses, potentially affecting the success of anesthesia. An educational intervention, such as an Operating Room (OR) Tour video, may alleviate anxiety by familiarizing patients with the surgical environment and process. Purpose: To determine the effect of an Operating Room Tour video on pre-anesthetic anxiety levels in CS patients. Methods: This study employed a pre-experimental design with a pretest-posttest approach to assess the impact of the video on pre-anesthetic anxiety in 30 CS patients at Cilacap General Hospital. Anxiety levels were measured using the Visual Analog Scale for Anxiety (VAS-A) before and after the intervention. Statistical analysis was conducted using the Wilcoxon signed-rank test to evaluate the significance of the change in anxiety levels. Results: The findings revealed a significant reduction in anxiety following the video intervention. Prior to the intervention, 43.3% of participants experienced moderate anxiety, while post-intervention, 66.7% reported only mild anxiety. The Wilcoxon test confirmed the significant impact of the OR Tour video on reducing pre-anesthetic anxiety (p = 0.011, p < 0.05). Conclusion: The use of an Operating Room Tour video is an effective strategy to reduce preoperative anxiety in CS patients. This educational intervention could be a valuable addition to pre-anesthesia care, improving patient comfort and potentially contributing to better surgical outcomes.